Differences in gastric microbiota and mucosal function between patients with chronic superficial gastritis and intestinal metaplasia - Li, Yingxia; Jiang, Libin; Li, Zhichao; Liu, Yali; Xiao, Bo; Ding, Yan; Wen, Hongtao (Frontiers in Microbiology, 2022)
Chronic superficial gastritis (CSG) and Intestinal metaplasia (IM) can further develop into gastric cancer, which seriously endangers the health of people all over the world. In this study, CSG and IM patients were diagnosed by NBI and WLI microscopy and HE staining, respectively. The difference of microbiota in gastric juice between CSG patients and IM patients was detected by 16S rRNA gene sequencing. The expression differences of mucin (MUC2 and MUC5AC) and CDX2 in gastric mucosa of CSG patients and IM patients were detected by Western blot. The results showed that the evolutionary diversity and richness of microbiota in gastric juice of CSG patients were significantly higher than those of IM patients. At the phylum level, the relative abundance of Thermi and Firmicutes in gastric juice of IM patients was significantly higher than that of CSG patients, while the relative abundance of Actinomycetes in CSG patients was significantly higher than that of IM patients. At the genus level, Thermous and Anoxybacillus were dominant in the gastric juice of IM patients, and Helicobacter was dominant in the gastric juice of CSG patients. While some CSG patients were accompanied by IM, accordingly, Helicobacter, Thermous and Anoxybacillus were detected in their gastric juice. The results of non-metric multidimensional scaling (NMDS) show that the dispersion of samples in CSG group is greater than that in IM group, and some samples in CSG group are clustered with samples in IM group. The KEGG metabolic pathway difference analysis of gastric juice microbiota in CSG and IM patients showed that the gastric juice microbiota in CSG and IM patients were significantly enriched in the metabolic pathway, and the functional differences between the two groups were mainly concentrated in the bacterial secretion system (VirB1, VirB2, VirB3, VirD1 and VirD4). Conclusion there are significant differences in the expression of gastric microbiota and mucin (MUC2 and MUC5AC) between CSG and IM patients. The results of this study can provide a new means for the detection of CSG and IM, and provide a new direction for the prevention and treatment of CSG and IM.